THEORETICAL MODELS OF ENSURING INTERDISCIPLINARY INTEGRATION AND CONTINUITY IN THE FORMATION OF PROFESSIONAL COMPETENCIES (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2026)
The fragmentation of educational content into isolated disciplinary silos remains one of the most significant barriers to the effective formation of professional competencies in modern vocational education. This article addresses the theoretical and methodological challenges of establishing interdisciplinary integration and pedagogical continuity within the curriculum. By analyzing the epistemological foundations of knowledge synthesis and the psychological mechanisms of skill transfer, the study argues that professional competence is inherently integrative and cannot be developed through a disjointed accumulation of subject-specific knowledge. The first section of this paper outlines the conceptual crisis of the "subject-centric" paradigm and establishes the theoretical imperatives for transitioning to an "integrative-modular" model, where the continuity of learning is maintained not merely through administrative sequencing but through the logical interconnection of cognitive and practical activities.